ST-elevation acute coronary syndromes in the Platelet Inhibition and Patient Outcomes (PLATO) trial: insights from the ECG substudy - Armstrong, Paul W.; Katus, Hugo (Circulation, 2012)
BACKGROUND: Ticagrelor, when compared with clopidogrel, reduced the 12-month risk of vascular death/myocardial infarction and stroke in patients with ST-elevation acute coronary syndromes intended to undergo primary percutaneous coronary intervention in the PLATelet inhibition and patient Outcomes (PLATO) trial. This prespecified ECG substudy explored whether ticagrelor's association with vascular death and myocardial infarction within 1 year would be amplified by (1) the extent of baseline ST shift and (2) subsequently associated with fewer residual ST changes at hospital discharge. METHODS AND RESULTS: ECGs were evaluated centrally in a core laboratory in 3122 ticagrelor- and 3084 clopidogrel-assigned patients having at least 1 mm ST-elevation in 2 contiguous leads as identified by site investigators on the qualifying ECG. Patients with greater ST-segment shift at baseline had higher rates of vascular death/myocardial infarction within 1 year. Among those who also had an ECG at hospital discharge (n=4798), patients with ≥50% ΣST-deviation (ΣST-dev) resolution had higher event-free survival than those with incomplete resolution (6.4% versus 8.8%, adjusted hazard ratio 0.69 (0.54-0.88), P=0.003). The extent of ΣST-dev resolution was similar irrespective of treatment assignment. The benefit of ticagrelor versus clopidogrel on clinical events was consistent irrespective of the extent of baseline ΣST-dev (P(interaction)=0.728). When stratified according to conventional times from symptom onset, ie, ≤3 hours, 3 to 6 hours, >6 hours, the extent of baseline ΣST-dev declined progressively over time. As time from symptom onset increased beyond 3 hours, the benefit of ticagrelor appeared to be more pronounced; however, the interaction between time and treatment was not significant (P=0.175). CONCLUSIONS: Ticagrelor did not modify ΣST-dev resolution at discharge nor was its benefit affected by the extent of baseline ΣST-dev. These hypothesis-generating observations suggest that the main effects of ticagrelor may not relate to the rapidity or the completeness of acute reperfusion, but rather the prevention of recurrent vascular events by more powerful platelet inhibition or other mechanisms. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00391872.